A Review for Arabic Extremism Detection Using Machine Learning - Sabri, Redhaa Fadhil; Abdullah, Nada A. Z. (Iraqi Journal of Science, 2024)
The detection of extremism is a field of research aimed at discovering extremism and hate speech on social networking sites through the use of natural language processing tools. Although this field is wide, there is little research in Arabic that has dealt with this topic compared to research in English, although a very large percentage of social media users are Arabs and interact in Arabic. In this research, the most important research works related to the field of extremism detection in the Arabic language using machine learning algorithms will be reviewed, and related works will be compared in terms of methodology and results.